Ilaban mo ... bayan ko! [videorecording] the Obet Pagdanganan story - Caparas, Carlo J.; Cruz, Lito; Villa, Donna (Golden Lions Films Production and UNI Films International, 1997)
Chronicles the life Governor Roberto "Obet" Pagdanganan who continues to lead Bulacan to progress and peace.